TAHALLI: MENGISI JIWA DENGAN SIFAT-SIFAT BAIK - Muspian Muspian (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Tahalli is an essential stage in the process of purifying the soul (tazkiyatun nafs) that plays a crucial role in the formation of noble character in Islam. Essentially, tahalli is the effort to beautify the soul with virtuous qualities after cleansing it from reprehensible traits through takhalli. Tahalli requires individuals to consciously and consistently instill values of goodness, both in their relationship with Allah and with fellow human beings. In practice, tahalli has a significant impact on both individual life and society. This process begins with strengthening faith and habituating oneself to practice virtuous character traits, such as sincerity, patience, trust in Allah, gratitude, and humility. The positive impacts of tahalli not only encompass inner peace but also improve social relationships, create a harmonious environment, and promote the development of a civilization based on moral values. Therefore, tahalli becomes a fundamental foundation in building an outstanding individual and a prosperous society.